Pharmacy Students' Perceived Ability to Implement the Pharmacist's Patient Care Process before and after a Redesigned Case Study Series in the United States - Amy Henneman; Samantha Axtell (MDPI AG, 2024)
Since the incorporation of the Pharmacist's Patient Care Process (PPCP) into the American Association of Colleges of Pharmacy standards, the process has been integrated in a variety of ways across curriculums. A two-semester case-based course was redesigned as a four-semester case-based course formally integrating the PPCP. Pharmacy students completing the original, two-semester course series and those completing the first two semesters of the redesigned course were given a voluntary survey to assess their perceived ability to integrate the PPCP into practice after the completion of each course. A total of 107 pharmacy students, 61 students completing the original series and 46 students completing two semesters of the redesigned series, completed the survey. The pharmacy students completing the redesigned, four-semester course series had a significantly higher perception of their ability to integrate the PPCP into patient care compared to the students completing the original series. This included the perceived ability to ask appropriate questions, identify medication-related problems (MRPs), document MRPs, and develop a plan for addressing MRPs. A significant difference was found in the students' perceived ability to ask pertinent questions in an appropriate manner, identifying and documenting MRPs, managing and solving MRPs, and documenting patient interactions. No significant difference was identified regarding the students' perceived ability to document the interaction or ensure that treatment-related plans were implemented. The students' perception regarding the importance of asking pertinent questions, identifying MRPs, and documentation in patient care did not differ between the cohorts. The case-based course series redesigned from two to four semesters with formal integration of the PPCP resulted in an increase in the students' perceptions of their ability to integrate the PPCP into patient care.